Task shifting of triage to peer expert informal care providers at a tertiary referral HIV clinic in Malawi: a cross-sectional operational evaluation - Megan Landes; Courtney Thompson; Edson Mwinjiwa; Edith Thaulo; Chrissie Gondwe; Harriet Akello; Adrienne K. Chan (BMC Health Services Research, 2017)
Abstract Background HIV treatment models in Africa are labour intensive and require a high number of skilled staff. In this context, task-shifting is considered a feasible alternative for ART service delivery. In 2006, a lay health cadre of expert patients (EPs) at a tertiary referral HIV clinic in Zomba, Malawi was capacitated. There are few evaluations of EP program efficacy in this setting. Triage is the process of prioritizing patients in terms of the severity of their condition and ensures that no harmful delays occur to treatment and care. This study evaluates the safety of task-shifting triage, in an ambulatory low resource setting, to EPs. Methods As a quality improvement exercise in April 2010, formal triage training was conducted by adapting the World Health Organization Emergency Triage Assessment and Treatment Triage Module Guidelines. A cross sectional observation study was conducted 2 years after the intervention. Triage assessments performed by EPs were repeated by a clinical officer (gold standard) to assess sensitivities, specificities, positive and negative predictive values for EP triage scores. Proportions were calculated for categories of disposition by stratifying by EP and clinician triage scores. Results A total of 467 patients were triaged by 7 EPs and re-triaged by clinical officers. With combined triage scores for emergency and priority patients we report a sensitivity of 85% and specificity of 74% for the EP scoring, with a low positive predictive value (41%) and a high negative predictive value (96%). We calculate a serious miss rate of EP scoring (i.e. missed priority or emergency patients) as 2.2%. Admission rates to hospital were highest among those patients triaged as emergency cases either by the EP’s (21%) or the clinicians (83%). Fewer patients triaged as priority by either EPs (5%) or clinicians (15%) were admitted to hospital, however these patients had the highest prevalence of same day lab testing and/or specialty referral. Conclusions Our study provides reassurance that in the context of adequate training and ongoing supervision, task-shifting triage to lay health care workers does not necessarily lead to less accurate triaging. EPs have a tendency to be more conservative in over-triaging patients.